2018
DOI: 10.1002/chem.201803330
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the First Spin Crossover in an Iron(II) Complex with an S6 Coordination Environment: Tris[bis(N,N‐diethylamino)carbeniumdithiocarboxylato]iron(II) Hexafluorophosphate

Abstract: For the first time, the spin-crossover (SCO) phenomenon has been observed in an Fe II -S 6 system in at ris-(chelate)-type iron(II) complexw ith az witterionic sulfur donor bidentate, bis(N,N-diethylamino)carbeniumdithiocarboxylate (EtL), [Fe II (EtL) 3 ](PF 6 ) 2 (1), as synthesized by the reaction of ap recursor complex [Fe II (CH 3 CN) 6 ](PF 6 ) 2 with EtL. In the solid state,t he high-spin (HS) d 6 state at ambient temperature and the low-spin (LS) d 6 state at temperatures lower than approximately 240 Kw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…At room temperature the complexes stabilized in the HS‐state show a μ eff value ranging from 4.9 to 5.5 μ B , although for the majority of complexes the value is higher than the expected μ S.O. =4.9 μ B , it is still in good agreement with the high spin state and suggests a considerable orbital contribution to g , [22,27,41] in addition the values are in agreement with the literature [20,42–44] . The room temperature μ eff value for complex 1 a containing the PySBn ligand (Figure 7) indicates that it is stabilized in the HS‐state, the μ eff value is maintained relatively constant down to 25 K, below this temperature zero field splitting (ZFS) is evident.…”
Section: Resultssupporting
confidence: 74%
“…At room temperature the complexes stabilized in the HS‐state show a μ eff value ranging from 4.9 to 5.5 μ B , although for the majority of complexes the value is higher than the expected μ S.O. =4.9 μ B , it is still in good agreement with the high spin state and suggests a considerable orbital contribution to g , [22,27,41] in addition the values are in agreement with the literature [20,42–44] . The room temperature μ eff value for complex 1 a containing the PySBn ligand (Figure 7) indicates that it is stabilized in the HS‐state, the μ eff value is maintained relatively constant down to 25 K, below this temperature zero field splitting (ZFS) is evident.…”
Section: Resultssupporting
confidence: 74%
“…The yellow plate-like single crystals (Figure S1a, Supporting , the second SCO hysteretic loop at lower temperature region becomes more symmetric, and the χ M T signal at 70 K is 0.08 cm 3 mol −1 K, indicative of a pure LS state, thus giving the complete hysteretic two-step SCO behavior with respective 9 K (T c1 ↓=123.4 K and T c1 ↑=132.4 K) and 25 K (T c2 ↓=94 K and T c2 ↑=119 K) thermal hysteresis loop. Such sweep rate dependent behavior indicates kinetic trapping [44,45] of the residual HS state in the second spin transition step for 1. Therefore, a further kinetic study was performed by cooling the sample to 110 and 90 K, respectively, with a cooling rate of 6 K min −1 and recording the evolution of the χ M T product as a function of time (Figure 1a inset).…”
Section: Resultsmentioning
confidence: 94%
“…= 4.9 μ B , it is still in good agreement with the high spin state and suggests orbital contribution to g , 22,42,43 in addition the values are in agreement with the literature. 6,9,44,45 The family of complexes containing the ImPyS ligand ( 1a–c , Fig. 6) showed a room temperature μ eff value ranging from 5.00 to 5.21 μ B , upon cooling the μ eff is maintained relatively constant down to c.a.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that S-containing ligands can be utilised to obtain iron(II) spin crossover (SCO) complexes [1][2][3][4][5][6][7][8][9][10][11][12][13] in some of which the iron(II) centres have a {N 4 S 2 } coordination sphere. SCO materials can reversibly switch between the high spin (HS) and low spin (LS) states by and external stimulus, such as temperature, pressure, applied magnetic field, light irradiation, solvation, etc.…”
Section: Introductionmentioning
confidence: 99%